Reticulate eruptions. Part 1: Vascular networks and physiology - Parsi, K.; Partsch, H.; Rabe, E.; Ramelet, Anne-Sylvie (2011)
Reticulate pattern is one of the most important dermatological signs of a pathological process involving the superficial vascular networks. Vascular malformations, such as cutis marmorata congenita telangiectasia and benign forms of livedo reticularis, and sinister conditions, such as meningococcal meningitis or Sneddon's syndrome, can all present with a reticulate pattern. The clinical presentation and morphology is determined by the nature and extent of the underlying pathology and the involvement of a particular vascular network. This review has been divided into four instalments. In the present paper, we discuss the anatomy and physiology of the complex network of vascular structures that support the function of the skin and subcutis.